Whether Audit Committee Financial Expertise Is the Only Relevant Expertise: A Review of Audit Committee Expertise and Timeliness of Financial Reporting (Issues in Social and Environmental Accounting (ISEA), 2013)
This study reviews the literature on audit committee expertise and financial reporting timeliness. Financial reporting timeliness and audit committee expertise are two areas of research gaining the attention of a large number of stakeholders because they contribute to the reliability and the relevancy of financial reporting. Indeed, the focus of this review is primarily on the recent developments in the pertinent literature in order to show the limitations of such research and encourage future research to overcome these limitations. By also looking at the development of the audit committee expertise literature, this study concludes that (1) like most audit committee literature, financial reporting timeliness literature continues to assume the absence of the contribution of expertise other than financial expertise, and ignore the role of audit committee chair; (2) most of this literature fails to find a significant effect because it ignores the interaction among corporate governance mechanisms. Accordingly, this study posits that ignoring the issues raised in such research by future research would lead to major mistakes in reforms relating to how the quality of financial reporting can be enhanced.